Isolasi dan Identifikasi Komponen Utama Minyak Atsiri dari Kulit Buah Jeruk Manis (Citrus sinensis L.) Asal Timor, Nusa Tenggara Timur - Siburian, Rikson (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2008)
Isolation and identifications of peel orange oils (Citrus sinensis, L.) which maserased by lard, coconut oil and mixof lard-coconut oil ( 2 : 1) has been done. This research aimed to obtain main component of peel orange oils fromTimor, knowing influence of lard, coconut oil and mix lard-coconut oils whom using as maserate to results ofchemistry components and atsiri’s oil rendemen product. In this research has been done by using maseration,extraction and using FT – IR and GC – MS as characterizations instruments. The results showed D- Limonen as amain component of atsiri oil from peel orange’s Timor.